Income and beyond : multidimensional poverty in six Latin American countries - Battiston, D; Cruces, G; Calva, L; Lugo, M; Santos, M (Oxford Poverty & Human Development Initiative (OPHI), 2009)
This paper presents empirical results of a wide range of multidimensional poverty measures for: Argentina, Brazil, Chile, El Salvador, Mexico and Uruguay, for the period 1992–2006. Six dimensions are analysed: income, child attendance at school, education of the household head, sanitation, water and shelter. Over the study period, El Salvador, Brazil, Mexico and Chile experienced significant reductions of multidimensional poverty. In contrast, in urban Uruguay there was a small reduction in multidimensional poverty, while in urban Argentina the estimates did not change significantly. El Salvador, Brazil and Mexico together with rural areas of Chile display significantly higher and more simultaneous deprivations than urban areas of Argentina, Chile and Uruguay. In all countries, access to proper sanitation and education of the household head are the highest contributors to overall multidimensional poverty.